A nova Política Nacional de Desenvolvimento Regional: construção, concepção e implementação - Santos, Kassya Karoline Fraga dos (2016)
The aim of this study is to analyze the new National Policy for Regional Development (PNDR II), with a focus on construction, design, organization and implementation, taking into account the National Integration Routes Program, which was conceived as a way to achieve the goals set by PNDR II. The relevance of the study is clear, given the fact that have been made in recent years some plans / policies, explicitly or implicitly, continuing the theme of regional socio-economic inequality. Thus, it is necessary to know whether the directives and guidelines of the New Regional Policy are aligned to the problem of regional inequality, as the results are often unsatisfactory achieved by previous policies. As a theoretical basis this work used as the basis Neo Schumpeterian thought of Innovation Systems and the structuralism of Cepal, under the figure of Raul Prebisch and Celso Furtado. The choice of the two theories is given by the observation points of convergence found in two thoughts. A highlight of these convergences can highlight the treatment of technical progress, such theories consider this development as a fundamental part for the development of a country or even a region. Another important point is how the specificities where knowing how to respect local potential, repudiating attempts to treat the development as a "cake recipe" are key factors. To carry out the work, as well as literature, also used up the desk research, analyzing documents relating to PNDR I, PNDR II, Routes Program National Integration, macro-regional study prepared by RedeSist for Routes Program. Also a field survey was carried out with semistructured questionnaire considered relevant actors within the Brazilian economy. Even from a methodological point of view the research was based on the development of economic policy as a cycle where macro form is divided into: Situational Analysis (problem recognition), Formulation (alternative for problem solution), Decision Making (trace goals - are the principles and guidelines), Implementation and Evaluation. Given that both the policy and the Routes Program are in its implementation phase, this research project stuck only the first four phases of the cycle. Research has shown that there is indeed a regional issue to be discussed and to be treated with a higher position, and that there is an alignment between the guidelines and principles proposed by the policy and what it chooses as a regional problem. It comes Routes Program was seen as a promising program to achieve the objectives of PNDR II, in view of the positive results that the Rota do Cordeiro has succeeded, for example, productive infrastructure and economic integration of producers of sheep and goats in the northeastern semi-arid.